Non-Matching Grids for a Flexible Discretization in Computational Acoustics (Communications in Computational Physics, 2020)
Flexible discretization techniques for the approximative solution of coupledwave propagation problems are investigated. In particular, the advantages of usingnon-matching grids are presented, when one subregion has to be resolved by a substantially finer grid than the other subregion. We present the non-matching grid technique for the case of a mechanical-acoustic coupled as well as for acoustic-acoustic coupled systems. For the first case, the problem formulation remains essentially the sameas for the matching situation, while for the acoustic-acoustic coupling, the formulationis enhanced with Lagrange multipliers within the framework of Mortar Finite ElementMethods. The applications will clearly demonstrate the superiority of the Mortar Finite Element Method over the standard Finite Element Method both concerning theflexibility for the mesh generation as well as the computational time.